PENGARUH SUMBER DAYA APARATUR, KOMITMEN ORGANISASI DAN PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS ALOKASI DANA DESA DI WILAYAH KECAMATAN UNDAAN KABUPATEN KUDUS - Ignatia Kusuma Cahyani, 15.05.52.0124; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2019)
Village Fund Allocation is funds allocated from Regency or City governments to villages. Accountability in managing village fund allocation is very important. This requires the village government to manage village fund allocations in a professional, effective and efficient manner. The purpose of this study was to examine and analyze the influence of apparatus resources, organizational commitment and internal control over the accountability of village fund allocations in the Undaan District district of Kudus Regency . This study uses primary data by giving questionnaires to respondents. The population is the apparatus involved in the village fund allocation in Undaan District, Kudus Regency, which consists of 16 villages. The research sample was in accordance with the criteria which amounted to 83 respondents. The sampling technique used was purposive sampling and the data analysis tool used was multiple linear regression analysis using SPSS 24 for window. The results of the study show that apparatus resources have no effect on the accountability of village fund allocations, while organizational commitment and internal control have an effect on the accountability of village fund allocations.